A cognitive model of digital transformation and IS decision making. (18th August 2020) - Russell, Kenneth; O'Raghallaigh, Paidi; McAvoy, John; Hayes, Jeremy
ABSTRACT: Individuals are complex bundles of thoughts, beliefs, emotions, and behaviours. For a digital transformation (DT) to be successful, it is necessary to understand how these bundles impact individuals' reactions to an impending change to then intervene to increase the likelihood of its success. Cognition is the mental action or process of acquiring understanding through thoughts, beliefs and emotions. Cognitive Models (CMs) describing these thoughts, beliefs, emotions and behaviours are applied and researched in psychology. On the other hand, the Information Systems (IS) domain is dominated by a behaviourist rather than a cognitivist approach. In this paper, we investigate what we can learn from these other sciences. By combining the research from the IS domain with that from the psychology domain, this paper presents a theoretical Cognitive Model for Digital Transformation (CMDT) that is a move towards explaining individual cognitive predispositions to DT and change decision making.